On-Field Performance of National Football League Players After Return From Concussion. (September 2014) - Kumar, Neil S.; Chin, Matthew; O'Neill, Craig; Jakoi, Andre M.; Tabb, Loni; Wolf, Michael
Background: There are few data examining the short-term effects of concussions on player performance upon return to play. This study examined changes in on-field performance and the influence of epidemiologic factors on performance and return to play. Hypothesis: On-field performance is different in players who return within 7 days after concussion compared with players who miss at least 1 game. Study Design: Case-control study; Level of evidence, 3. Methods: Players in the National Football League who were active during the 2008 to 2012 seasons were considered for inclusion. Weekly injury reports identified concussed players. All players played in at least 4 games before and after the game of injury (sentinel game) within the year of injury (sentinel year). Players who had missed games secondary to another injury or had sustained a second concussion within the sentinel year were excluded. The players' league profiles were used to determine age, position, body mass index, career experience, and games missed. ProFootballFocus performance scores determined player ratings. Statistical analysis used 2-sided t tests and both univariate and multivariate logistic regression models. Results: There were a total of 131 concussions in the 124 players who qualified for this study; 55% of these players missed no games. Defensive secondary, wide receiver, and offensive line were the most commonly affected positions. Players who missed at least 1 game were younger and less experienced. Preinjury ProFootballFocus performance scores were similar to postinjury performance in players without games missed (0.16 vs 0.33; P = .129) and players who missed at least 1 game (−0.06 vs 0.10; P = .219). Age, body mass index, experience, and previous concussion did not correlate with changes in postinjury scores ( P > .05). Older, more experienced players and players with late-season concussions were more likely to return to play without missing games ( P < .05). The odds of returning within 7 days increased by 18% for each career year and by 40% for each game before the sentinel game within the sentinel year; these same odds decreased by 85% after introduction of newer treatment guidelines in 2009. Conclusion: No difference in player performance after concussion was found whether the player did or did not miss games before return. Return without missing games may be associated with experience and timing of injury within a season and less likely after newer guidelines.